Economic Growth and The Environment In Malaysia - Rasiah, Rajah; Shazali, Abu Mansor; Abas, Said (Universiti Malaysia Sarawak, (UNIMAS), 2002)
The debate on economic growth and the environment has continued to draw considerable passion. Economists tend to be dominated by the Kuznets inverted "U" shaped curve expositions that contend that environmental conditions tend to deteriorate until a certain per capita threshold income is reached after which they will improve (see World Bank. 1992; Panayotou, 1993; Antle and Heidebrink, 1995; Seldon and Song, 1994). However, sustainable development arguments originating from green groups in the North claim that the South economies should avoid the growth path of the North so as to avoid environmental catastrophe, premised on the argument that environment costs are difficult to estimate and prices cannot be apportioned to living matter. This position is pervasively pushed at the World Trade Organisation (WTO) where some insist that trade should be linked to environmental standards. To gamer sUpJX>rt from the South, there has been a push to expand development assistance to assist them to strengthen environment-friendly production capabilities. Critics argue that this effort is a double whammy for developing economies, at one level restricting the independence of South's development JX>licies, and at another level merely opening demand for the North's environment-friendly technologies. It is extremely difficult to ignore the contention that environmental costs cannot be assessed against income levels as it will not be in sync with normative definitions of development. However, given that economic activities typically generate emissions, it is not sufficient to just remove them all together. While taking cognisance of the need to prevent the proliferation of environmentally hazardous emissions, it might still be worth re-examining the Kuznets curve. Indeed it is interesting to see if latecomers shorten the time period, threshold per capita incomes and pollution intensities given rising awareness and the growth of environment-friendly technologies. However, while these are interesting exercises, this paper looks at Malaysia to see if the Kuznets curve trends are being replicated. This paper attempts to contribute to this literature by examining economic growth and the evolution of environmental governance in Malaysia. The next section introduces the analytical framework. The following section discusses economic transition in Malaysia, followed by its corollary on the environment The subsequent section deals with its impact on the environment, including governance.